3-day mortality in hospitalised community-acquired pneumonia: frequency and risk factors. Issue 5 (25th February 2016) - Kolditz, Martin; Bauer, Torsten T.; König, Thomas; Rohde, Gernot; Ewig, Santiago
Mortality of hospitalised patients with community-acquired pneumonia (CAP) continues to be high and efforts have been made to characterise a subgroup of patients with an emergency presentation defined by a high risk of early clinical deterioration or death in order to target initial management interventions to patients with a high potential of prognosis improvement [1–3]. However, the actual magnitude of an emergency presentation in CAP remains unclear as the most severely affected patients are frequently underrepresented in prospective studies [1, 3]. Additionally, early mortality within 3 days in CAP only rarely has been studied so far [3–5]. The aim of the present analysis was to characterise patients dying within 3 days after hospitalisation for CAP using the unique database of the German nationwide mandatory quality assurance programme, which requests all hospitals in Germany to document all cases hospitalised with CAP according to a pre-specified electronic data sheet. 3-day mortality from CAP corresponds to 33% of in-hospital deaths; the CRB-65 criteria are independent predictors http://ow.ly/XFMlB